Traditions and innovations in assessment of glomerular filtration rate using creatinine to cystatin C. Issue 1 (11th January 2023) - Tio, Maria Clarissa; Shafi, Tariq; Zhu, Xiaoqian; Kalantar-Zadeh, Kamyar; Chan, Alexandre; Nguyen, Lee
Abstract : Purpose of review: Glomerular filtration rate (GFR) is the best index for kidney function and estimated GFR (eGFR) calculated from endogenous filtration markers like serum creatinine and cystatin C is widely used in clinical practice for chronic kidney disease diagnosis and prognostication. We sought to review the evolution of GFR estimating equations, nuances of eGFR interpretation, and utility of eGFR in drug dosing. Recent findings: The Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) serum creatinine eGFR equation was recently updated to exclude the race variable and the CKD-EPI creatinine–cystatin C equation demonstrated the highest reliability. Although calculated creatinine clearance by Cockcroft Gault has been traditionally used for drug dosing, the use of eGFR is slowly being adapted by the Food and Drug Administration for pharmacokinetic studies. However, the individual-level accuracy of eGFR using the CKD-EPI 2021 equations remained low, with the distribution of measured GFR at a given eGFR value spanning several CKD stages. Summary: Although current methods of estimating GFR have improved in population measures of reliability, all have significant individual-level inaccuracies that can be an issue when clinical decision-making is contingent on the actual level of GFR. Modern methods of GFR measurements should be made widely available to enhance individualized patient decision-making.